IOT PADA MONITORING WATER LEVEL MENGGUNAKAN ESP8266 - sjahrul, yurika; Zuhud, Adji Muhaemin (Jurnal TEDC; Vol 17 No 1 (2023): JURNAL TEDC, 2023)
Filling the water reservoir is still done manually, so the water level in the reservoir cannot be known and causes the reservoir to overflow or empty. Sometimes people forget to turn off the water pump when the water reservoir is full, causing air to be wasted. From these problems, it is necessary to make a tool that can be controlled automatically. This automatic control works so that it can be used for electricity use so that the motor can only be at the levels that have been set as needed. IOT-based monitoring and controlling of water levels using the esp8266 microcontroller can make it easier to carry out the process of observing and controlling in real time. This control system uses a water pump that functions to install water in the tank and the water level sensor will detect the water in the tank. the presence of water in the tank will be displayed on the LCD which serves as an indicator. Based on the results of the study, it can be said that the water tank filling system can control the water level in the tank automatically at low, medium, and high conditions. The test results in 5 trials, the average difference between the height of the blynk application and the actual distance from all experiments that have been carried out is 0.84 cm. And the average relative error yields 4.8%.